Exploration of the interchromosomal effects in preimplantation genetic testing for structural rearrangements based on next‐generation sequencing. Issue 9 (8th August 2022) - Fan, Junmei; Zhang, Xueluo; Chen, Yanhua; Zhang, Junkun; Zhang, Lei; Bi, Xingyu; Wang, Jinbao; Huang, Xiang; Yan, Meiqin; Wu, Xueqing
Abstract: Background: To investigate the interchromosomal effect (ICE) in chromosome translocation carriers. Methods: Data on preimplantation genetic testing aneuploidy and structural rearrangements (translocation) were retrospectively collected and classified into a reciprocal translocation group, a Robertsonian translocation group and a control group. According to the carrier's gender and age, all cases underwent further subgroup difference analysis of de novo abnormal embryo rates and the number of chromosomes involved in de novo abnormal embryos. Results: Among the 283 couples who participated in this study, 1076 blastocysts from 352 cycles were collected, and 246 de novo abnormal embryos were included. There was a significant difference in the rate of de novo abnormal embryos among the three groups ( p < .05) but no significant difference in the number of de novo abnormal chromosomes in the abnormal embryos ( p > .05). Gender and age (classified by 35 years old) had no effect on the de novo abnormal embryo ratios among the translocation carriers ( p > .05). However, the de novo abnormal ratio increased with age. The embryo constitution reflected no significant difference between the translocation groups ( p > .05). Conclusion: The ICE was detected for the translocation carriers. The de novo abnormal embryo ratio increased with age. Gender had no effect on the de novo abnormal embryo ratio. Translocation status played a more important role than age and gender. Abstract : The difference of de novo abnormal embryo ratio was significant among three groups( p > .05). There was significant difference in the de novo abnormal ration between control group and reciprocal translocation ( p > .05), was significant difference in the de novo abnormal ration between control group and Robertsonian translocation ( p > .05), and was no significant difference between reciprocal translocation group and Robertsonian translocation group( p > .05). ICE exists for couples with chromosomal translocation.